以马内利二校幼儿园在线汉语情况分析 - Kristina Sucilita; Lily Thamrin; Suhardi Suhardi (Universitas Tanjungpura, 2022)
AbstractDuring the Covid 19 Pandemic. The learning process cannot be carried out at school but online. Online learning refers to teaching and learning environment (virtual classroom). Immanuel II Christian Kindergarten using the Microsoft Teams application in the Online Learning Process. The method used by the author is the method of questionnaires and interviews. While the purpose of this research is to determine the condition and problems that often occur during online learning. Online learning very effective for now because children can still go to school even though online, Based on the questionnaire, the condition of learning Mandarin online reached 64.37%. then online learning also has frequent problems. What happens is that the network consumes a lot of quota or mobile data. By questionnaire problems that often occur reach 72.74%.Keywords: kindergarten, mandarin learning, online learning